Interface engineering of two-dimensional transition metal dichalcogenides towards next-generation electronic devices: recent advances and challenges. Issue 5 (4th March 2020) - Liao, Wugang; Zhao, Siwen; Li, Feng; Wang, Cong; Ge, Yanqi; Wang, Huide; Wang, Shibo; Zhang, Han
Abstract : This review presents recent advances and challenges in the interface engineering of 2D TMDCs and emerging electronics based on TMDCs. Abstract : Over the past decade, two-dimensional (2D) transition metal dichalcogenides (TMDCs) have attracted tremendous research interest for future electronics owing to their atomically thin thickness, compelling properties and various potential applications. However, interface engineering including contact optimization and channel modulations for 2D TMDCs represents fundamental challenges in ultimate performance of ultrathin electronics. This article provides a comprehensive overview of the basic understanding of contacts and channel engineering of 2D TMDCs and emerging electronics benefiting from these varying approaches. In particular, we elucidate multifarious contact engineering approaches such as edge contact, phase engineering and metal transfer to suppress the Fermi level pinning effect at the metal/TMDC interface, various channel treatment avenues such as van der Waals heterostructures, surface charge transfer doping to modulate the device properties, and as well the novel electronics constructed by interface engineering such as diodes, circuits and memories. Finally, we conclude this review by addressing the current challenges facing 2D TMDCs towards next-generation electronics and offering our insights into future directions of this field.